Effects of population density on growth and production of Tilapia in monoculture (International Journal of Agricultural Research, Innovation and Technology, 2018)
The experiment was conducted to determine the effect of population density on growth and production of Tilapia (monosex GIFT tilapia) in monoculture system for a period of 110 days. The experiment was carried out in six earthen ponds, which were situated in the Bangladesh Agricultural University Campus, Mymensingh. The experiment was carried out under three treatments each with two replications. Fish population density was 200 fish per decimal under treatment-I, 400 fish per decimal under treatment-II and 600 fish per decimal under treatment-III. In the ponds supplementary feed of wheat bran and rice bran mixture were used daily at the rate of 46 g, 92 g and 136 g per decimal under treatment-I, II, and III, respectively. The average initial length and weight of tilapia were 4.63 cm and 2.82 g respectively. The ponds were fertilized fortnightly with urea and TSP at the rates of 60 g and 90 g, respectively. During experimental period, the ranges of water temperature (25.82 to 29.80 ºC), transparency (28.00 to 38.00 cm), dissolved oxygen (5.50 to 8.30 mg/L), pH (7.00 to 7.90), total alkalinity (130.00 to 200.00 mg/L), free CO2 (2.00 to 6.00 mg/L), phosphate-phosphorus (1.20 to 2.30 mg/L), and nitrate-nitrogen (3.20 to 4.00 mg/L) were within the productive range and more or less similar in all the ponds under three treatments. There were 25 genera of phytoplankton under five major groups and 10 genera of zooplankton under three major groups in the experimental ponds. Mean survival rate of fish under treatment-I, treatment-II, and treatment-III were 82.75%, 77.12% and 74.33% respectively. The calculated net fish production under treatment-I was 6.75 ton/ha/yr and that of the ponds under treatment-II was 10.26 ton/ha/yr and that of the ponds under treatment-III was 12.15 ton/ha/yr. The net fish production under treatment-II and treatment-III were 152% and 180% higher than that of treatment-I, taking net fish production under treatment-I for 100%. According to profit-cost analysis, the ratios of net profit under treatments I, II, and III were 1:0.44, 1:0.27, and 1:0.09. According to specific growth rate and survival, treatment-I is the best, and according to profit-cost analysis treatment-I (ratio 1:0.44) also the best. So, the population density of 200 fish per decimal (under treatment-I) might be considered the best among the three treatments.Int. J. Agril. Res. Innov. & Tech. 7 (2): 49-56, December, 2017